2012
DOI: 10.1002/jcp.22843
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib sensitizes hepatocellular carcinoma cells to physiological apoptotic stimuli

Abstract: Sorafenib increases survival rate of patients with advanced hepatocellular carcinoma (HCC). The mechanism underlying this effect is not completely understood. In this work we have analyzed the effects of sorafenib on autocrine proliferation and survival of different human HCC cell lines. Our results indicate that Sorafenib in vitro counteracts autocrine growth of different tumor cells (Hep3B, HepG2, PLC-PRF-5, SK-Hep1). Arrest in S/G2/M cell cycle phases were observed coincident with cyclin D1 down-regulation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
73
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 43 publications
8
73
0
2
Order By: Relevance
“…Consistent with the previous studies, the cell cycle analysis suggested that the AF4 induced G2/M phase arrest in HepG2 cells (Fig. 5) signifying mitosis arrest; whereas chemotherapy drug Sorafenib showed a S/G2-M phase arrest which was consistent with previous finding (28). This confirms that the AF4-induced cell death is cell-cycle regulated.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with the previous studies, the cell cycle analysis suggested that the AF4 induced G2/M phase arrest in HepG2 cells (Fig. 5) signifying mitosis arrest; whereas chemotherapy drug Sorafenib showed a S/G2-M phase arrest which was consistent with previous finding (28). This confirms that the AF4-induced cell death is cell-cycle regulated.…”
Section: Discussionsupporting
confidence: 91%
“…28 BBC3 is a proapoptotic BH3-only protein that can sensitize HCC cells to sorafenib-induced apoptosis. 29 Some tumor-promoting genes such as MYC, 30 EGFR, 31 VEGFA, 32 and NOTCH1 33 are downregulated by PP2Ac silencing. These results offer a molecular insight into the regulation of the aggressiveness of HCC by PP2Ac.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of Bak contributes to the development and progression of HCC [28,29]. The significance of Bak in HCC cells is further supported by several experiments in which different agents induce apoptosis in HCC cells by stimulating Bak expression [3033]. Although the significance of Bak in HCC has been reported, the mechanism responsible for its regulation in HCC is largely unknown.…”
Section: Discussionmentioning
confidence: 99%